Efficient removal of per- and polyfluoroalkyl substances (PFASs) in drinking water treatment: nanofiltration combined with active carbon or anion exchange. Issue 11 (26th June 2019) - Franke, Vera; McCleaf, Philip; Lindegren, Klara; Ahrens, Lutz
Abstract : Nanofiltration produces potable water, while adsorption materials GAC and AIX remove more PFASs from membrane retentate than from raw water. Abstract : Society's increasing use of chemicals poses a challenge for drinking water producers. Accepted concentrations for per- and polyfluoroalkyl substances (PFASs) in finished water are lower than ever before with new regulations often enacted based on findings made possible by improved analytical techniques and correspondingly justified health concerns. Nanomembrane filtration removes compounds, including PFASs, based primarily on size-exclusion, however, treatment and/or disposal of PFAS laden membrane concentrate remains a challenge. This study combined feedwater nanofiltration with granular activated carbon (GAC) and anion exchange (AIX) for concentrate treatment. Nanofiltration removed PFAS concentrations on average by 99% including some PFASs with molecular weights smaller than the membrane nominal cutoff of 270 Da, indicating membrane rejection mechanisms additional to size-exclusion. Treatment of raw water and concentrate was compared in column tests. AIX showed up to threefold greater half-time of saturation than GAC, however with a higher rate of decreasing efficiency, while GAC removed approximately 20% of incoming PFAS concentrations consistently after treatment of 15 000 bed volumes (BVs). Overall, GAC and AIX removed 2.6-fold and 4.1-fold more PFAS mass per adsorbent volume from the concentrated retentate than from raw water indicating that the combination of nanofiltration with GAC or AIX increases the efficiency of the adsorbent materials in comparison to only using GAC or AIX filters.